Partisipasi Masyarakat dalam Pembangunan di Desa Puuwonua - Rezky Syaputri (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2022)
Aim of this research is how is community participation in development in Puuwonua Village, Kec. Konawe Kab. Konawe and to find out how community participation in development in Puuwonua Village, Kec. Konawe Kab. Konawe. The research approach used is a qualitative research approach. The informants of this study were 11 (eleven) people consisting of: the village head, the village secretary, the head of the BPD, members of the BPD, the head of the hamlet, 2 (two) head of the RT, the head of youth, and 3 (three) people from the community. The techniques used in collecting research data are interviews, observation, and documentation. The technique used in the analysis of research data is qualitative with the stages of reducing data and presenting data. The results showed that community participation in Puuwonua Village, Kec. Konawe Kab. Konawe, namely where (1) community participation based on thoughts is still very minimal in the Musrembang and RPJMDes processes; (2) community participation based on labor is still low in contribution in the form of energy in mutual cooperation and community service activities; (3) community participation based on expertise, people tend to be apathetic due to lack of understanding and awareness; (4) community participation based on goods, the community has participated by lending tools or equipment but the quality is not good; and (5) community participation based on funds, the community has not been able to participate directly in the form of cash in cash but the community can provide basic food for ongoing development. Development in Puuwonua Village, Kec. Konawe Kab. Konawe is where (1) Village development is based on physical development, several types of existing development, both facilities and infrastructure that can be used by the local community for their welfare; and (2) Village development based on non-physical development of several types of existing development in the form of counseling that can be followed by local communities to increase knowledge. More about this source text Source text required for additional translation information Send feedback Side panels.